Homogenous vs. heterogenous transition functions in smooth transition regressions: A LM-type test - Matei Demetrescu; Julian Sebastian Leppin; Stefan Reitz (Kiel Institute for the World Economy (IfW), 2017)
(Panel) Smooth Transition Regressions substantially gained in popularity due to their flexibility in modeling regression coefficients as homogeneous or heterogeneous functions of transition variables. In the estimation process, however, researchers typically face a trade-off in the sense that a single (homogeneous) transition function may yield biased estimates if the true model is heterogeneous, while the latter specification is accompanied by convergence problems and longer estimation time, rendering their application less appealing. This paper proposes a Lagrange multiplier test indicating whether the homogeneous smooth transition regression model is appropriate against the competing heterogeneous alternative. The empirical size and power of the test are evaluated by Monte Carlo simulations.
Keywords: C52; C22; C12; 330; STR model; multivariate; nonlinear models; testing